Work-based Learning through School Production Unit in Polytechnic Institutes - Thapa, Harish Singh (Journal of Technical and Vocational Education and Training, 2023)
Work-based learning (WBL) is a planned activity that integrates learning and work together to develop knowledge and skills for future employment. The study focuses on exploring WBL in the school production unit, which is a part of the school laboratory that works for the production of goods, items, or provision of services. This paper synthesizes, compares and contrasts the approaches of the WBL in production unit with the help of the literature through a systemic literature review. The production unit in Technical and Vocational Education and Training (TVET) institutes has been found as a contributive factor to experiential learning, active learning employability and entrepreneurship skills, work-based sustainability for students, and increased cooperation/collaboration learning ability of students. These are major applications of the implementation of WBL through school production units in TVET schools. The paper concludes that TVET education institutions anticipate the production-based modality to ensure the sustainability of WBL.